Redescriptions of two species and descriptions of three new species of the louse genus Bizarrifrons Eichler, 1938 (Phthiraptera: Ischnocera: Philopteridae) - Valim, Michel P.; Palma, Ricardo L. (Zootaxa, 2012)
Redescriptions of Bizarrifrons magus (Nitzsch [in Giebel], 1866), the type species of Bizarrifrons, and B. picturatus Car-riker & Díaz-Ungría, 1961 are given based on material from their type hosts. The nymphal instars of these two species aredescribed and illustrated for the first time. Also, three new species are named and described: B. latifrons, from the russet-backed oropendola, Psarocolius angustifrons alfredi (Des Murs, 1856); B. wecksteini, from the Amazonian oropendola,Psarocolius b. bifasciatus (Spix, 1824); and B. quasisymmetricus, from the solitary cacique, Cacicus solitarius (Vieillot,1816) (Passeriformes: Icteridae). Two species-groups are proposed, and a checklist and a key for the species of Bizarri-frons are also included. Sequences of a portion of the mitochondrial cytochrome oxidase I (COI) and the nuclear elongation factor 1α (EF-1α) genes for two species are given for the first time in this genus.